Hydrotreatment over the Catalyst of Polyethylene-Derived Pyrolysis Oil and Wax - Hafeez, Sanaa; Van Haute, Maarten; Manos, George; Karam, Hajar Jawad; Constantinou, Achilleas; Al-Salem, Sultan Majed (My University, 2023)
Upgrading fuels is an essential requirement to reach environmental specifications, namely, in removing sour components deemed hazardous nowadays and that cause fouling and disturb operations in downstream industry too. A lack of studies that report fundamental data also exist in the literature, as to the impact of hydrotreatment on thermochemical conversion products of plastics. We hereby report for the first time in this communication the effect of hydrotreatment on the products of plastic pyrolysis. Two types of pyrolysis products, oils and wax, were extracted from fluidized bed reactor pilot-plant operations at two operating temperatures (600 and 700 °C). These were subjected to hydrotreatment in a batch reactor over a Pt/Al2O3 catalyst for 6-8 h. Dependent upon the sample type, the hydrotreatment temperature reached 350 °C and was initialized at 140 °C. The hydrotreatment reactor handles a 180 barg pressure, and the operating pressure was kept steady in operation during measurements. The pressure rates (0.29-0.62 bar h-1), which decreased with the temperature (140-200 °C), were also recorded. The olefinic compounds were saturated from wax post-hydrotreatment and detected by alteration of carbon singular and double bond existence. Naphthalene and paraffins were also eliminated from oils treated, as confirmed by infrared spectroscopy and chromatography. The conversion during the hydrotreatment reduced the reactivity of the pyrolysis oil and promoted the production of diesel and kerosene production. It is therefore recommended to extend these types of studies using different catalysts that can provide environmental specifications to fuels with minimal costs in the near future as an essential route for integrated operations in industry.